83 Evaluation of transmammary-delivered firocoxib and an ethyl chloride spray to mitigate pain associated with processing procedures in piglets. (30th November 2020) - Viscardi, Abbie V; Shirtcliff, Elizabeth; Eppler, Emily; Miller, Savannah; Coetzee, Johann
Abstract: Piglets raised in commercial production systems in the U.S. undergo painful management procedures, including surgical castration, tail docking and ear notching, without analgesia or anesthesia provision for pain relief. This is a significant animal welfare concern. There is an immediate need to identify the most practical and effective analgesia or anesthesia option for use on-farm. The objective of this study was to assess the efficacy of 2.0mg/kg firocoxib, administered to the sow and delivered transmammary to her piglets, and a vapocoolant spray (ethyl chloride) to reduce processing pain. Five-day old male and female Yorkshire-cross piglets were used. 2.0mg/kg firocoxib was administered to the sow intramuscularly 7h prior to processing piglets. An ethyl chloride spray was applied to the ears, tail and scrotum of the piglets immediately before ear notching, tail docking and surgical castration, respectively. Piglets were assigned to one of four treatment groups: firocoxib and vapocoolant spray (FV; n=32), firocoxib only (F; n=32), vapocoolant spray only (V; n=32), no treatment (CON; n=32). The observation period was from 24h pre- to 48h post-processing (specific time points = baseline, 0h, 1h, 2h, 4h, 7h, 24h, 30h, 36h, 48h). Preliminary results found piglets displayed significantly more pain-related behaviors at 24h and 30h post-processing than at most other time points (p< 0.05). Piglets had significantly higher cranial temperatures at 7h post-processing than all other time points (p< 0.05). There was a trend in FV and F piglets having a higher cranial temperature at 36h post-processing compared to V and CON piglets (p=0.08). All piglets had significantly higher hair cortisol levels at 4 vs 20-days old (p< .0001); however, there were no significant treatment effects on cranial temperature, hair cortisol or pain behavior, suggesting firocoxib and the ethyl chloride spray were unable to significantly reduce piglet pain post-processing. Further study analysis is needed to confirm these initial findings.